Digital Literacy: Utilization of the TikTok Platform as an Arabic Language Learning Media to Increase Vocabulary Knowledge - Mochammad Mu’izzudin; Siti Nuryulia; Siti Tsamrotul Fuady; Azka Al-Ghifari Akmal (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2024)
Lack of Arabic vocabulary knowledge is a challenge in classroom learning. Students need a good understanding of vocabulary to translate Arabic texts, but their interest in looking up the meaning of words in the dictionary is low. As a generation familiar with digital media, students are more interested in social media. Therefore, this study aims to analyze the use of learning media to increase interest in digital literacy positively by utilizing the TikTok application as a potential solution to help students expand their Arabic vocabulary knowledge effectively. This type of research is field research with qualitative approach, data collection techniques in the form of observation and documentation, while the assessment instrument tools used are pretests and posttests on student learning outcomes related to vocabulary knowledge. The subjects in this study were TikTok content videos selected based on their relevance to the vocabulary learning theme. The results of the study showed that 60% of the results of the survey of students' learning interests mostly chose TikTok as the social media technology platform of choice, while the pre-test results were 20% of students who were in the high score category, and increased in the post-test to 90% after the implementation of TikTok learning media, this can show that TikTok not only improves students' learning outcomes in terms of mastery of Arabic vocabulary, but can also increase interest in digital literacy which is good for learning.